Long‐term morbidity and mortality in patients with Cushing's syndrome. (21st March 2022) - Braun, Leah T.; Vogel, Frederick; Reincke, Martin
Abstract: Increased multisystem morbidity and mortality in patients with Cushing's syndrome comprise clinical problems and challenges, both at the time of diagnosis and in remission. Relevant comorbidities and clinical problems include hypertension, diabetes, overweight, myopathy and a high risk for acute complications such as infections and venous thrombembolism. Although there are therapy recommendations for most of these comorbidities, there is a lack of large, prospective studies to confirm and optimise them. Mortality is especially high during active disease and within the first year after diagnosis, as a result of cardiovascular events, infections and suicide. All in all, interdisciplinary therapy management is important for reducing morbidity and mortality over the long‐term.